Hyphotetical Learning Trajectory: Pemecahan Masalah Materi Sistem Persamaan Linear Dua Variabel - Rezky, Raizal; Jais, Ernawati (Mandalika Mathematics and Educations Journal, 2020)
One of the goals of mathematics learning mentioned by NCTM is to become a mathematical problem solver. This indicates that students who study mathematics will have problem-solving abilities. In solving problems the things that need to be considered in learning are more about the process than the final result. If the final answer is emphasized, students can only learn one particular problem Furthermore, the important mathematical material is a two-variable linear equation system because the learning process in SPLDV requires good mastery of the material in problem solving, so from here it is necessary to design learning in order to formulate precisely the learning patterns that will be carried out by the teacher to students. This research uses design research method at the preliminary design stage which is arranged by considering students' ability to solve a mathematical problem at SMPN 1 Sampolawa, because each student has a different way of thinking between one student and another student. The flow of students' thinking that might appear in learning is called the hypothetical learning trajectory. In this article will explain the Hypothetical Learning Trajectory (HLT) in students' problem solving activities material systems of linear equations of two variables.AbstrakSalah satu tujuan pembelajaran matematika yang disebutkan oleh NCTM yakni menjadi problem solver matematika. Hal ini mengindikasikan siswa yang mempelajari matematika akan memiliki kemampuan pemecahan masalah. Dalam memecahkan masalah hal yang perlu diperhatikan dalam belajar adalah lebih mengutamakan proses dari pada hasil akhir. Jika jawaban akhir yang ditekankan maka siswa hanya dapat belajar satu masalah tertentu Selanjutnya materi matematika yang penting adalah sistem persamaan linear dua variabel (SPLDV) ini dikarenakan proses pembelajaran pada SPLDV memerlukan penguasaan materi yang baik dalam pemecahan masalah, sehingga dari sini diperlukan desain pembelajaran agar dapat merumuskan secara tepat pola pembelajaran yang akan dilakukan oleh guru kepada siswa. Penelitian ini menggunakan metode design research pada tahap preliminary design yang disusun dengan mempertimbangkan kemampuan siswa dalam menyelesaikan suatu masalah matematika di SMPN 1 Sampolawa, karena tiap siswa memiliki cara berpikir yang berbeda antara siswa satu dengan siswa yang lain. Alur berpikir siswa yang mungkin muncul dalam pembelajaran dinamakan dengan hipotesis lintasan belajar atau hypothetical learning trajectory. Dalam artikel ini akan memaparkan Hypothetical Learning Trajectory (HLT) dalam kegiatan pemecahan masalah siswa materi sistem persamaan linear dua variabel.